Longitudinal, reciprocal effects of social skills and achievement from kindergarten to eighth grade. Issue 4 (August 2015) - Caemmerer, Jacqueline M.; Keith, Timothy Z.
Abstract Previous research suggests that students' social skills and achievement are interrelated, and some findings support bi-directional effects between the two constructs. The purpose of this research study was to estimate the possible longitudinal and reciprocal effects of social skills and achievement for kindergarten through eighth grade students. Data from the Early Childhood Longitudinal Study program were analyzed; teachers' ratings of students' social skills and students' standardized math and reading achievement performance were collected 4 and 5 times, respectively. Latent variable structural equation modeling was used to test a panel model of reciprocal, longitudinal effects of social skills and achievement. The results suggest that the effects of students' social skills and achievement are bi-directional, but the effects of students' achievement on their later social skills are stronger than the effects of social skills on achievement. The significant effects of students' social skills on their later achievement are mostly indirect. These findings suggest that the future social skills of students who struggle academically may be of particular concern to educators, and intervention and prevention efforts aimed to address both social and achievement skills may help remediate the other skill in the future.